Overview of Green Nanofabrication Technologies for Food Quality and Safety Applications. Issue 1 (2nd January 2023) - Pandhi, Shikha; Mahato, Dipendra Kumar; Kumar, Arvind
ABSTRACT: Green nanotechnology has emerged as a sustainable fabrication technology that has offered tremendous frontiers in the field of food science. This review intends to provide a succinct overview of various green nanofabrication technologies including green creation of nanoparticles using biological sources explicitly from plants as natural reducing agents. In addition, the review explores various biocompatible nano delivery systems for nanoencapsulation of food ingredients for enhancing the sensorial and functional properties food products. Promising applications based on these approaches employing active and smart packaging systems, nanosensors along with functional foods for ensuring food quality and safety have been briefly outlined. Abbreviations: AgNPs: Silver nanoparticles; EOs: Essential Oils; Nm: Nanometer; NPs: Nanoparticles; NLC: Nanostructured lipid carrier; (O/W): Oil-in-water; NLC: Nanostructured lipid carrier; PHB: Poly (3-hydroxybutyrate); PVA: Polyvinyl alcohol; RFID: Radiofrequency identification; SARS: Severe Acute Respiratory Syndrome; SLN: Solid lipid nanoparticles; UV-Visible: Ultraviolet–visible; (W/O): Water-in-oil